Does real interest rate reduce income inequality in India? Evidence from multivariate framework analysis - Muhammed Ashiq Villanthenkodath; Mantu Kumar Mahalik (European Journal of Government and Economics (EJGE), 2022)
This study empirically examines the impact of real interest rate on income inequality in India within a Kuznets Curve framework considering the role of economic growth, trade openness and technological innovation as the control variables. This study employs the ARDL bounds test for validating the long-run relationship over the annual data period 1995 to 2019. The results reveal the long-run relationship between the series in India. The findings suggest that the initial increase in interest rate significantly reduces income inequality. But, in a later stage, a threshold exists for such an increased interest rate to revert the prior beneficial impact. This finding further shows that Kuznets' inverted U-shaped hypothesis is not valid for the relationship between income inequality and real interest rate in India. It shows that the real interest rate impedes income distribution in the long run. These findings are also found to be robust using FMOLS and DOLS estimators. We find that economic growth significantly reduces income inequality, whereas trade openness promotes it. Surprisingly, technological innovation enhances income inequality, but this effect vanishes in the long-run. However, these findings suggest that policymakers in India should not ignore the impeding role of real interest rates while aiming at achieving effective income distribution between haves and have-nots in the long run.
Keywords: D63; E49; O40; O53; 330; income inequality; interest rates; economic growth; India